The Differences of Improving Junior High School Student’s Creative Thinking Ability Through The Relating, Experiencing, Apllying, Cooperating, Transferring (REACT) Strategy and Conventional Learning Model - Harahap, Ellyana Sari (Advances in Social Sciences Research Journal, 2018)
This study aims to determine (1) the differences in the improvement of students' mathematical creative thinking skills by the relating, experiencing, applying, cooperating, transferring (REACT) strategies better significantly compared to conventional learning models, (2) the interaction between learning approaches and initial mathematcl ability in improving students' creative thinking skills, this type of research is quasi-experimental. This research was carried out at SMP Negeri 1 Medan. The population in this study were all eighth grade students by taking a sample of two classes. The instruments used consisted of PMA tests and tests (pretest and posttest) with indicators of students' creative thinking abilities. The instrument was declared to have fulfilled the requirements of content validity and a high reliability coefficient of 0.83 on the ability to think creatively. Data were analyzed by ANACOVA test and two-way ANOVA. Before using the ANACOVA and ANOVA two-way test, homogeneity in the study was first tested and normality in this study was 5% significance level. The results showed that: (1) there were differences in the improvement of creative thinking abilities of students who were given learning using REACT strategies better than using conventional learning. This can be seen from the results of covariance analysis (ANACOVA) for F count 69.53 greater than F table 4.00. The regression equation constant for REACT learning is 8,297 greater than conventional learning that is 6,192 (2) there is no interaction between the learning model with the students 'initial mathematical ability to increase students' creative thinking skills.